Generation, culture and flow-cytometric characterization of primary mouse macrophages - Schleicher, Ulrike; Bogdan, Christian (Macrophages and Dendritic Cells: Methods and Protocols, 2009)
Macrophages are not only host cells for many pathogens, but also fulfill several key functions in the innate and adaptive immune response, including the release of pro- and anti-inflammatory cytokines, the generation of organic and inorganic autacoids, the phagocytosis and killing of intracellular microorganisms or tumor cells, and the degradation and presentation of antigens. Several of these functions are shared by other immune cells, including dendritic cells, granulocytes, NK cells, and/or T lymphocytes. Thus, the analysis of macrophage functions in vitro using primary mouse cell populations requires standardized methods for the generation and culture of macrophages that guarantee high cell purity as well as the absence of stimulatory microbial contaminants. This chapter presents methodology to achieve these aims. © 2009 Humana Press, a part of Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2024-02-26
Keywords: Bone marrow-derived macrophages; Cell sorting; Cytokines; Flow cytometry; Interferon-gamma; Macrophages; Peritoneal exudate macrophages; Resident peritoneal macrophages; Teflon bags